Reliability Analysis of the Slope Stability of Homogeneous Earth Dam under Seismic Loading - Belazouz, Lynda; Bouzelha, Karima; Hammoum, Hocine; Amiri, Ouali; Khelil, Nacim (Periodica Polytechnica Civil Engineering, 2024)
Earth dams are widespread throughout the world and their safety is the overriding concern of civil engineers, especially in regions with high seismic activity. This contribution presents a deterministic and reliability-based approach of the slope stability analysis of homogeneous earth dam under seismic loading. The hydrostatic loading as well as the saturation line in the dam body is considered for different design situations to investigate the effects of water level fluctuations on earth dam slope stability. Seismic loading is introduced by horizontal and vertical pseudo-static forces, while the considered failure mode is circular slip, analyzed with the classical method of slices. Given the nature of the soils, uncertainties about their properties must be considered in the assessment of the slope stability. These uncertainties can be quantified by a reliability analysis. The proposed reliability method is approached by the failure probability assessment of the slope stability of an earth dam based on Monte-Carlo simulation. The used random variables are the mechanical shear properties of the embankment body as well as the acceleration coefficient of the seismic zone. For the failure probability evaluation, the log-normal distribution law was used to generate the random variables. A computer program was developed using Matlab®. The developed approach was applied, for a practical example, to analyze the slope stability of an earthen dam located in Médéa (Algeria), whose dimensions are realistic. The results obtained with the developed analytical model were compared with those obtained with the Flac2D© software. The confrontation turned out to be satisfying.